The Influence of Intangible Assets, Tax Expenses, and Profitability on Transfer Pricing Indications - Oktaviani, Novia; Mukhtar (Management Science Research Journal, 2024)
This research aims to determine the effect of intangible assets, tax expenses, and profitability on transfer pricing. The population of this research is multinational companies listed on the Indonesian Stock Exchange during the 2017-2021 period. The method used purposive sampling with a total sample of 44 research data. This study uses secondary data based on the financial statements of multinational companies obtained from the Indonesia Stock Exchange website. The analysis technique used is multiple linear regression. The result of this research shows that intangible assets do not affect transfer pricing. Meanwhile, tax expenses and profitability have a positive effect on transfer pricing.